Protective Strategies and Emotions Invested in Early Modern Danish Christening Garments. (3rd May 2016) - Mathiassen, Tove Engelhardt
Abstract: In 2006–2007, Den Gamle By, National Open Air Museum of Urban History and Culture in Denmark staged a large exhibition of christening garments dating from the eighteenth century until the present. It was called "Christian Clothing and Baptismal Robes over 300 years." More than 100 objects were exhibited. Garments for babies remind us of the vulnerability of the newborn and in this way they are emotional objects for us today and probably also in the past. Elements of vulnerability are especially obvious for modern viewers when the garments originate from earlier periods with much higher infant mortality rates than today. Parents in earlier centuries used various strategies to protect their small pagans from exposure to evil before baptism. In this way emotions were invested in the garments, but it is a challenge to access and analyze these emotions because the garments themselves do not constitute a language in the same way as written texts. The article will deal with three different material elements which might be considered protective strategies for babies. The first and longest part of the article presents the color red as a means of protection. The next section considers the use of metal as protection against evil and coins as vehicles of good fortune. The third and shortest section discusses the reuse of ritual garments in new ceremonial contexts. When their provenance is known, it is striking that several baptismal garments represent a reuse of garments from weddings or other rites de passage, as termed by Arnold van Gennep.